Rafts and Other Rivercraft : in Huckleberry Finn - Beidler, Peter G. (Book collections on Project MUSE., 2018)
In this book, structured largely as a series of answers to rhetorical questions about the nomenclature and physical makeup of rivercraft in Mark Twain's works and elsewhere, Beidler exerts complete salvage rights over the raft itself. Beidler's detailed annotations give us a solid grub stake for grasping the material culture of Huck Finn and, thus, enlarging our understanding of the book as a whole. --Jacket.